2019
DOI: 10.7150/ijms.32105
|View full text |Cite
|
Sign up to set email alerts
|

Falls rate increase and foot dorsal flexion limitations are exhibited in patients who suffer from asthma: A novel case-control study

Abstract: Purpose: Based on the possible association between reduced foot dorsiflexion and high risk of falls, the main objective was to determine the ankle and 1º metatarsophalangeal joint (1 st MTTP) dorsiflexion range of motion and falls rate in patients with asthma compared to healthy matched-paired controls. Methods: A case-control study was carried out. Eighty participants were recruited and divided into patients with asthma (case group; n=40) and matched-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In studies conducted on diseases that cause widespread chronic pain such as low back pain, knee osteoarthritis, and fibromyalgia, it has been observed that as the severity of pain increases, the balance ability deteriorates, postural stability oscillations increase, and risk of falling and fear of falling increase [ 9 , 11 13 , 28 , 29 ]. Patients with respiratory problems [ 20 , 21 ] and patients with foot problems [ 30 ] have also been shown to have increased fall risk. However, the number of studies looking at this relationship was limited in shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies conducted on diseases that cause widespread chronic pain such as low back pain, knee osteoarthritis, and fibromyalgia, it has been observed that as the severity of pain increases, the balance ability deteriorates, postural stability oscillations increase, and risk of falling and fear of falling increase [ 9 , 11 13 , 28 , 29 ]. Patients with respiratory problems [ 20 , 21 ] and patients with foot problems [ 30 ] have also been shown to have increased fall risk. However, the number of studies looking at this relationship was limited in shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…Literature studies have shown results such as age being associated with the risk of falls, pain in the musculoskeletal system and falls and also a relationship between pain and balance is shown [ 9 , 13 15 , 19 ]. Falls are a great concern for most patient groups, including even patients with respiratory problems, who also experience pain and musculoskeletal disorders which results in increased fall risk [ 20 , 21 ]. However, there is little published research investigating the relationship between different levels of shoulder pain, balance ability, falling risk and fear of falling, involving all age groups diagnosed with musculoskeletal shoulder problem.…”
Section: Introductionmentioning
confidence: 99%
“…It is argued that the use of custom foot orthoses reduces instability improves performance and gait quality [10]. Identifying early which alterations of the foot can change their kinematics is important so that it can be compensated as soon as possible and, consequently, prevent injury and risk of falling in the future [11].…”
Section: Introductionmentioning
confidence: 99%
“…The foot posture index is a validate tool to assessment a normal foot posture normal supinated or pronated. On the other hand, there is no consolidated evidence between the relationship between the position of the pronated foot and its impact on the spatiotemporal gait parameters and, consequently, a lack of coordination and risk of falling [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation